(untitled) (Journal of Mechanical Engineering, 2013)
The static pressure distributions on a single of cylinder with octagonal cross-section having rounded corners are presented. The test was conducted in an open circuit wind tunnel at a Reynolds number of 4.13 x 104 based on the face width of the cylinder across the flow direction in a uniform flow velocity of 13.2 m/s. The experimental test was carried out on a single cylinder at various angles of attack from 0° to 40° at a step of 5°. It was observed that with the rounded corners the drag on the cylinders reduces remarkably in comparison to that on the sharp-edged cylinders. It was also observed that at various angles of attack, the values of the lift coefficients were insignificant compared to those for a sharp-edged square cylinder. The results are applicable to combination of tall buildings one behind the other along the wind velocity direction and each building of square or octagonal cross-section having rounded corners. The wind load on the downstream cylinder decreases remarkably due to the presence of the cylinder in the upstream side. DOI: http://dx.doi.org/10.3329/jme.v43i1.15767